The 6+1 Trait Writing Model to Build Up Students’ Writing - Kalsum (EDUVELOP, 2020)
This study aims to investigate the effectiveness of the 6+1 trait writing model and its impacts on students' writing achievement. It is focused on the students' improvement based on the five processes of writing which connected with analytic rubrics six-trait. Writing is the activity that requires students to systematically follow step by step to get professional results. Systematically compiled writing can help the reader to understand what the writer wants to convey. Writing requires an assessment to determine whether the writing is good or not. Writing appraisals can be categorized based on the assessment rubric that used. Analytic rubric six-trait is able to provide a detailed assessment and covers all aspects of the writing phase. To get the aim of the study, this study implemented experiment research by quantitative methods. The study was conducted on students’ of PondokPesantren DDI At-TaqwaJampuePinrang by using written tests. Based on the analysis, it is found that the students' writing was improved in four categories out of six categories. It can be seen by looking at the t-test which is higher than the t-table value for each category. The analytic rubric six trait may be a tool to measure the students' writing improvement based on the six categories in the writing element.